Viewing the impact of Brexit on Britain's financial centre through an historical lens: Can there be a third reinvention of the City of London? - Gary Arthur Dymski; Maria Gavris; Gissell Huaccha (ZFW - Advances in Economic Geography, 2023)
This paper considers the question of how Brexit will affect the City of London from a long-term perspective, putting the changes induced by Brexit into the context of the City's historical evolution over the past century. This perspective permits us to see that the City has continued to thrive because of a series of radical adjustments necessitated by the UK's loss of its empire and by the emergence of global US financial power. Challenges to the global prominence of the City in Britain's post-empire period have required two separate 'reinventions': the first, in the 1960s, involved localizing the Eurodollar markets; the second, in the 1990s, involved making London the preferred hub for providing sophisticated financial services within the European Union (EU)'s single market. The Great Financial Crisis put in motion several economic and political dynamics that have, however, undercut the City's special global role. It is unclear whether maintaining the City's offshore focus via a third reinvention, in a period of prolonged stagnation and increasing inequality in UK regions outside London, will be possible.
Keywords: 330; Brexit; City of London; Euromarkets; European Union; Great Financial Crisis; Offshore banking; single market